2011
DOI: 10.1021/bc2002874
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Transfection Efficiency of Cationic Oligopeptide Lipids: Role of Linker

Abstract: In the design of new cationic lipids for gene transfection, the chemistry of linkers is widely investigated from the viewpoint of biodegradation and less from their contribution to the biophysical properties. We synthesized two dodecyl lipids with glutamide as the backbone and two lysines to provide the cationic headgroup. Lipid 1 differs from Lipid 2 by the presence of an amide linkage instead of an ester linkage that characterizes Lipid 2. The transfection efficiency of lipoplexes with cholesterol as colipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 42 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…48,49 In our study, we used two structurally different conjugates (Tf–PEI and Tf-PEG-PEI) which were comparable in physicochemical properties but different in transfection, binding, and uptake efficiencies. As a result, the efficiency of PEI conjugates strongly depends on the linker chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 In our study, we used two structurally different conjugates (Tf–PEI and Tf-PEG-PEI) which were comparable in physicochemical properties but different in transfection, binding, and uptake efficiencies. As a result, the efficiency of PEI conjugates strongly depends on the linker chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In this light, Vacus and co-workers suggested that the ability of amide linkers to form intermolecular hydrogen bonding is responsible for the high melting temperature of the lipids and for the lipoplex stability (Boukhnikachvili et al, 1997). Such speculations were later confirmed by Gopal et al, who demonstrated that amide-bearing cationic lipids were much more stable and effective in transfection than ester-tethered transfectants (Gopal et al, 2011).…”
Section: Amidesmentioning
confidence: 97%
“…This was followed by the addition of complexes to the wells in a triplicate manner, and the cells were allowed to incubate in the CO 2 incubator for about 4 h. The complex media were replaced by 10% serum media (0.3 mL per well) and the incubation was continued for about 48 h in a CO 2 incubator and assayed by following the protocol, as mentioned earlier. 46 Furthermore, to support the transfection patterns obtained from beta gal transfection, one more transfection was performed using the pEGFP-N 3 plasmid in HEK-293 and CHO cells. Briefly, the cells were seeded onto a 12-well plate at a density of 4 × 10 4 cells per well a day before the transfection.…”
Section: Transfection Biologymentioning
confidence: 99%